Ecotourism-Based Mangrove Conservation Strategy in Cemara Beach, Banyuwangi Regency - Irwan Kurniawan Soetijono; Rudi Mulyanto; Marwiyah Marwiyah; Syafriza Akbar; Chyntabela Puspita Martha (Airlangga University, 2021)
Mangrove forest management is important for environmental conservation efforts in coastal areas. The purpose of this study was to determine the activities of mangrove forest rehabilitation and sustainable mangrove forest management strategies through ecotourism at Cemara Beach, Banyuwangi Regency. This study used a survey approach as well as direct interviews and field observations. The impact caused by the rehabilitation of mangrove forests in the study area is increasing fish catches, reducing coastal abrasion, resisting sea breezes, and increasing the number of types of biota catches in the form of shrimp, shellfish, and crabs around the mangroves. Another impact is the increase in the attractiveness of the fir beach so that it is worthy of being used as a tourist attraction, especially eco-based tourism. The strategies that need to be carried out in the management of mangrove forests include planting mangrove trees, strengthening coastal management institutions, increasing human resources (HR) for fishing groups, increasing collaboration with stakeholders, diversifying the income of women fishermen from Cemara Beach, and innovating eco-based tourist attractions. Ecotourism at Cemara Beach, Banyuwangi Regency.Keywords: Ecotourism, Mangrove, Cemara Beach, Conservation strategy.